2019
DOI: 10.31234/osf.io/f7q64
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Thin White Line: Adaptation suggests a common neural mechanism for judgements of Asian and Caucasian body size

Abstract: Visual adaptation has been proposed as a mechanism linking viewing images of thin women’s bodies with body size and shape misperception (BSSM). Non-Caucasian populations appear less susceptible to BSSM, possibly because adaptation to thin Caucasian bodies in Western media may not fully transfer to own-race bodies. Experiment 1 used a cross-adaptation paradigm to examine the transfer of body size aftereffects across races. Large aftereffects were found in the predicted directions for all conditions. The strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As in the current study, cross-adaptation was also demonstrated, suggesting that the selectivity for self/other was only partial. In contrast, Gould-Fensom et al (2019) were unable to show any contingent body size and shape adaptation using bodies from different racial groups (East Asian and Caucasian). A demonstration of 100% cross-adaptation between bodies from the two groups in a second experiment confirmed that the neurons are race-agnostic, suggesting that the lack of contingent aftereffects is likely to be due to substantial transfer and cancelation of aftereffects that are opposite in direction.…”
Section: Discussionmentioning
confidence: 70%
“…As in the current study, cross-adaptation was also demonstrated, suggesting that the selectivity for self/other was only partial. In contrast, Gould-Fensom et al (2019) were unable to show any contingent body size and shape adaptation using bodies from different racial groups (East Asian and Caucasian). A demonstration of 100% cross-adaptation between bodies from the two groups in a second experiment confirmed that the neurons are race-agnostic, suggesting that the lack of contingent aftereffects is likely to be due to substantial transfer and cancelation of aftereffects that are opposite in direction.…”
Section: Discussionmentioning
confidence: 70%
“…Visual adaptation studies have done much to uncover the details of the processes that underlie the perception of body size and shape. Neural substrates have been shown to be high-level, nonretinotopic structures (Brooks et al, 2018) whose neurons show some selectivity for identity (e.g., self vs. other: Brooks et al, 2016) and gender (Brooks, Baldry, et al, 2019) but do not discriminate on the basis of race (Gould-Fensom et al, 2019). There also appear to be independent neural populations responsible for the perception of fat and muscle mass.…”
Section: Resultsmentioning
confidence: 99%
“…As was the case with self/other, aftereffects were found to transfer partially between stimuli of different genders, suggesting that the neural mechanisms responsible for our perception of body size and shape are partially sex-selective (Brooks, Baldry, et al, 2019). However, when adaptors and test stimuli differed in terms of race (here, representing White and East Asian subjects whose faces were clearly visible), aftereffects were just as large as when adaptors and test stimuli belonged to the same racial group (Gould-Fensom et al, 2019). This suggests that those same neural mechanisms are race-insensitive, at least for the two racial categories used in this study.…”
Section: From Media To Mirror: Viewing Others’ Bodies Causes Mispercementioning
confidence: 99%
See 1 more Smart Citation
“…As in the current study, cross-adaptation was also demonstrated, suggesting that the selectivity for self/other was only partial. In contrast, (Gould-Fensom et al, 2019) were unable to show any contingent body size and shape adaptation using bodies from different racial groups (East Asian and Caucasian). A demonstration of 100% cross-adaptation between bodies from the two groups in a second experiment confirmed that the neurons are race-agnostic, suggesting that the lack of contingent aftereffects is likely to be due to substantial transfer and cancellation of aftereffects that are opposite in direction.…”
Section: Discussionmentioning
confidence: 70%